Molecular Characterisation of Very Virulent Infectious Bursal Disease Virus and the Effects of Its Viral Proteins on Cancer Cell Lines - Voon, Kenny Gah Leong (2005)
Infectious bursa1 disease virus (IBDV) is an immunosuppressive virus causing bursa lesions and atrophy. There are several strains of IBDVs, namely classical, variant, attenuated and very virulent strains. Viral proteins, VP2 and VP5, from attenuated strain had been shown to induce apoptosis in chicken embryo fibroblast (CEF) and African green monkey cell line (BSC40). The objective of this study is to characterise local isolate IBDV namely, UPMOIIIO and to determine the apoptotic effect of VP2 and VP5 proteins in neoplastic and normal cell lines. UPMOIIIO was successfully characterised as vvlBDV, based on the molecular methods. The VP2 sequence of UPMOIIIO isolate had amino acid substitutions at Ala[222], [lle]256, [He1294 and [Ser]299, similar to other reported vvlBDV. This isolate did not have Lys[249] and Ser[254] amino acid residues which had been reported to be present in variant strains. The deduced amino acids of VP2 showed that the two hydrophilic regions and the serine-rich heptapeptide region were conserved in UPMOll10. Similar finding was reported for other vvlBDVs such as UK661, HK46 and OKYM. The VP2 nucleotides sequence of UPMO1110 could be cut by restriction enzymes Taql, Accl, Styl, Spel but not by Sacl. UPMO1/10 showed highest homologous similarity in nucleotides and amino acids to the reported Malaysian vvlBDVs. Phylogenetic analysis based on the nucleotides sequence of the VP2 and VP5 revealed that UPMO1110 isolate was clustered with other very virulent strains but distanced with classical, variant and attenuated strains. Serial samples of Chang, HepG2 and MCF-7 cells transfected with VP2 or VP5 at the interval of 6, 12, 18 and 24 hours were examined, respectively, in order to identify the onset of apoptosis. VP2 and VP5 of UPMO1110 were successfully expressed in Chang, HepG2 and MCF-7 cells. VP2 or VP5 alone was capable of triggering apoptotic response in Chang, HepG2 and MCF-7 cells. The onset of apoptosis started at 6 hours and preceded to necrosis at 24 hours. Both Chang and HepG2 cells were significantly susceptible to either VP5 or VP2 as compared to MCF-7 cells. VP5 induced significantly prominent apoptosis in HepG2 as compared to Chang cells at 6 hours, followed by maintaining similar level of apoptosis in both cells from 12 to 24 hours. However, VP2 induced higher level of cell death significantly in Chang cells as compared to HepG2 cells with exception at 6 hours. VP5 may be possible to be taken into consideration as candidate for liver cancer therapy as compared to VP2.